A novel COF-based Cu heterogeneous catalyst for a green Suzuki cross-coupling reaction under mild conditions. (18th January 2023) - Feng, Hui-Jun; Sun, Xue; Wang, Jun-Wen
Abstract : A novel Cu-based "single atom" heterogeneous catalyst for a Suzuki cross-coupling reaction at room temperature with excellent yield was synthesized. Abstract : The design and development of a low-cost and sustainable catalytic system to replace expensive Pd-catalysts for the Suzuki cross-coupling reaction is one of the major challenging areas of research in synthetic organic chemistry. Cross-coupling reactions with good yield in the presence of the Cu-based monometallic catalyst at room temperature have not been realized in previous works. We herein report the fabrication of a novel "single-atom" Cu catalyst (Cu-TAPB-BTDA-COF) for the Suzuki-coupling reaction at room temperature. The catalyst was obtained by post-synthetic metalation of the COF, synthesized by the combination of 4, 4′-(benzothiadiazole-4, 7-diyl)dibenzaldehyde (BTDA) and 1, 3, 5-tris-(4-aminophenyl)-benzene (TAPB). Cu-TAPB-BTDA-COF shows excellent catalytic activity for the Suzuki cross-coupling reaction, which is able to effectively promote the Suzuki cross-coupling reaction under mild reaction conditions (room temperature, a nontoxic solvent, and air atmosphere). In addition, the catalyst could be recycled and reused multiple times without the loss of catalytic activity. Compared with other Cu-based catalysts, our COF-based Cu catalyst simultaneously demonstrates excellent performance and recyclability.